Orchid inventory in Bantimurung-Bulusaraung National Park, South Sulawesi, Indonesia - DWI MURTI PUSPITANINGTYAS (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Puspitaningtyas DM. 2017. Orchid inventory in Bantimurung-Bulusaraung National Park, South Sulawesi, Indonesia. Biodiversitas 18: 341-350. Bantimurung-Bulusaraung National Park, commonly abbreviated as Babul National Park, is in South Sulawesi. It occupies an area of 43,750 hectares between 119o34'17"-119o55'13" East and 4o42'49"-5o06'42" South. Babul National Park is an area in the transition zone between Asia and Australia and therefore has a unique flora and fauna. The study reported here aimed to inventory the orchid species in the Babul National Park area and to determine the orchid diversity in the area. The results of the study recorded approximately 60 orchid species found in Babul National Park. These were representative of 32 genera and consisted of 42 species of epiphytic orchids and 18 species of terrestrial orchids. The terrestrial orchid Habenaria beccarii and the epiphytic orchid Aerides inflexa were the most common orchids found, and were spread evenly throughout the Babul National Park area. Coelogyne celebensis and Aerides inflexa are endemic orchids of Sulawesi found within the Park. Three species of the genus Nervilia, i.e. N. punctata, N. plicata, and N. aragoana, were also found in this area. Some species of orchid such as Tropidia angulosa, Coelogyne rumphii and Dendrobium lampongense were found as new records in Sulawesi. Keywords: Bantimurung-Bulusaraung National Park, inventory, orchid, South Sulawesi